Leisure time physical activity participation in individuals with spinal cord injury in Malaysia: barriers to exercise - Mat Rosly, Maziah; Halaki, Mark; Hasnan, Nazirah; Mat Rosly, Hadi; Davis, Glen Macartney; Husain, Ruby (Springer Nature, 2018)
Study design: Cross-sectional. Objectives: An epidemiological study describing leisure time physical activities (LTPA) and the associations of barriers, sociodemographic and injury characteristics to moderate-vigorous aerobic exercise participation among individuals with spinal cord injury (SCI) in a developing Southeast Asian country. Setting: SCI community in Malaysia. Methods: The study sample consisted of 70 participants with SCI. Questionnaires were distributed containing an abbreviated Physical Activity Scale for Individuals with Physical Disabilities (items 2–6) and the Barriers to Exercise Scale using a 5-tier Likert format. Statistical analyses were χ 2 tests, odds ratios, and binary forward stepwise logistic regression to assess the association and to predict factors related to participation in moderate-vigorous intensity aerobic exercise (items 4 and 5). Results: Seventy-three percent of the study sample did not participate in any form of moderate or vigorous LTPA. The top three barriers to undertaking LTPA (strongly agree and agree descriptors) were expensive exercise equipment (54%), pain (37%) and inaccessible facilities (36%). Participants over the age of 35 years, ethnicity, health concerns, perceiving exercise as difficult and indicating lack of transport were significantly different (p < 0.05) between participation and non-participation in moderate-vigorous aerobic exercise type of LTPA. Age, ethnicity, indicated health concerns and lack of transport were the significant predictors in likelihood of participating in moderate-vigorous LTPA (p < 0.1). Conclusion: The issues raised depicted barriers within the intrapersonal (health concerns, exercising is too difficult, pain while exercising, age more than 35), interpersonal (different ethnicity), community (expensive exercise equipment), and policy levels (lack of or poor access to transportation, inaccessible facilities) that prevent LTPA participation.